Rose Boland, 1969 (1969)
1969 1960-2000 "Rose Boland, 1969" [EP0115], 1969 The cover of 'Socialist Woman' for May-June 1969 carries a photograph of Rose Boland, one of the prominent women involved in the 1968 sewing machinists' strike at the Ford Motor Company.